The epidemiology of pelvic ring fractures in Qatar - Mohamed H. Elamin (21633638) (2024)
Purpose This study aimed to determine the incidence of pelvic ring fractures and their associated epidemiological profile in Qatar. Methods A retrospective cross-sectional study was performed at the only level I trauma centre in Qatar for patients diagnosed with pelvic ring fractures between January 2016 and December 2018. Age, sex, mechanism of injury, fracture classification and associated characteristics, mode of treatment, associated nerve injuries, and other complications were analyzed. Results A total of 327 consecutive patients were included, with an average age of 32.6 years. Most of the included patients were males, 85% (279), with a male: female ratio of 6:1. The incidence of pelvic fractures was 3.887/100,000 across the three years. High-speed motor vehicle collisions (MVC) were the most common mechanism of injury (108, 33%), followed by falling from height (105, 32%). Young-Burgess lateral compression (LC) fracture type was the most frequent (224, 68.5%) and was associated with 25% of the entire mortalities. Nine (2.8%) cases were open fractures, and 12% (39) were deemed unstable. Around 29% of cases had associated injuries, with an overall mortality rate of 4.9% (16) observed. Most fractures were treated nonoperatively(n = 283,86.5%). Conclusion This study demonstrated the epidemiology of pelvic fractures in Qatar. MVC and work-related injuries were predominant in a younger cohort compared to the literature. Also, the mortality rate was lower than those reported in the literature. Therefore, well-trained surgeons and specialized trauma centres for treating these injuries are recommended. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-024-06103-w